Market Segmentation Based on Psychography of Novi Dapur Rice Bowl Consumers - Ramadhan, Novita Ayunani Victoria; Hendrawan, Dimas (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze market segmentation based on psychographics of consumers at Rice Bowl Dapur Novi in Malang City. The method used is quantitative descriptive with a survey. The study population is consumers of Rice Bowl in Malang City with a sample of 140 people. The data analysis technique uses the K-Means Cluster. The results show that there are four consumer segments with different psychographic characteristics. The first segment named The idealism, the second segment named The enthusiastic, the third segment named The incurios, and the fourth segment named The phlegmatic . This research provides insights for the owners of Rice Bowl Dapur Novi to develop targeted marketing strategies.